2016
DOI: 10.3389/fpls.2016.01815
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Aquaporins in Setaria viridis Stem Development and Sugar Storage

Abstract: Setaria viridis is a C4 grass used as a model for bioenergy feedstocks. The elongating internodes in developing S. viridis stems grow from an intercalary meristem at the base, and progress acropetally toward fully expanded cells that store sugar. During stem development and maturation, water flow is a driver of cell expansion and sugar delivery. As aquaporin proteins are implicated in regulating water flow, we analyzed elongating and mature internode transcriptomes to identify putative aquaporin encoding genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 122 publications
1
5
0
Order By: Relevance
“…PePIP1;6 , PePIP2;7 , and PeTIP1;3 were co-expressed with four types of sugar transporter genes, including PLT , SUC / SUT , SWEET , and pGlcT . These results were similar to those co-expressed genes involved in water and sugar transport-related processes in the developing grass stems of Setaria viridis [ 35 ], which indicated that the PeAQP s might participate in the regulation of bamboo shoot growth through water and sugar transport, which would require further studies.…”
Section: Resultssupporting
confidence: 78%
“…PePIP1;6 , PePIP2;7 , and PeTIP1;3 were co-expressed with four types of sugar transporter genes, including PLT , SUC / SUT , SWEET , and pGlcT . These results were similar to those co-expressed genes involved in water and sugar transport-related processes in the developing grass stems of Setaria viridis [ 35 ], which indicated that the PeAQP s might participate in the regulation of bamboo shoot growth through water and sugar transport, which would require further studies.…”
Section: Resultssupporting
confidence: 78%
“…This is more critical for perennial species, because it will allow essential non‐foliar structures to avoid senescence while not limiting reproductive development and productivity. Additionally, in bioenergy grasses, the accumulation of stem sugars is essential for productivity (Feltus & Vandenbrink, 2012), such that enhancing export to stems has been proposed as a target trait for improvement in these crops (McGaughey et al, 2016). As we have previously discussed, however, sugar transport activity is impaired by heat stress, thereby highlighting the importance of stem and ear photosynthesis in such situations.…”
Section: The Capacity Of Non‐foliar Photosynthesis To Contribute To Yield and Reproductive Development During Heat Stressmentioning
confidence: 99%
“…Both OsTIP1;1 and OsTIP2;2 have water channel activity when expressed in yeast cells. The transcription levels of SvPIP2;1 are also very high in the elongating stem in Setaria viridis [ 90 ] ( Figure S1 ). Based on these observations, it is plausible that these PIPs, SIPs and especially TIPs as water transporters function in hypocotyl and stem growth.…”
Section: Roles Of Aqps In Vegetative Growthmentioning
confidence: 99%